Behaviour intention to use the learning management: integrating technology acceptance model with task-technology fit - Zadeh, Sousan Baleghi; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini; Mohd Daud, Shaffee (IDOSI Publications, 2014)
In recent years many higher education institutes have equipped themselves with Learning Management System (LMS). Although LMS supports the process of teaching and learning, its utilization by students is limited. The present study integrated task-technology fit with Technology Acceptance Model to predict behavior intention to use of Learning Management System among higher education students. The sample size of the study included 316 undergraduate students from two local university nearby in Malaysia. To find the better fit, partially-mediated and fully-mediated models were compared through Structural Equation Model. The results of data analysis revealed that the partially-mediated model got the better fit.